Metabolic engineering of Escherichia coli for the production of l -valine based on transcriptome analysis and in silico gene knockout simulation - Jin Hwan Park; Kwang Ho Lee; Tae Yong Kim; Sang Yup Lee (2007)
The l -valine production strain of Escherichia coli was constructed by rational metabolic engineering and stepwise improvement based on transcriptome analysis and gene knockout simulation of the in silico genome-scale metabolic network. Feedback inhibition of acetohydroxy acid synthase isoenzyme III by l -valine was removed by site-directed mutagenesis, and the native promoter containing the transcriptional attenuator leader regions of the ilvGMEDA and ilvBN operon was replaced with the tac promoter. The ilvA , leuA , and panB genes were deleted to make more precursors available for l -valine biosynthesis. This engineered Val strain harboring a plasmid overexpressing the ilvBN genes produced 1.31 g/liter l -valine. Comparative transcriptome profiling was performed during batch fermentation of the engineered and control strains. Among the down-regulated genes, the lrp and ygaZH genes, which encode a global regulator Lrp and l -valine exporter, respectively, were overexpressed. Amplification of the lrp , ygaZH , and lrp-ygaZH genes led to the enhanced production of l -valine by 21.6%, 47.1%, and 113%, respectively. Further improvement was achieved by using in silico gene knockout simulation, which identified the aceF , mdh , and pfkA genes as knockout targets. The VAMF strain (Val Δ aceF Δ mdh Δ pfkA ) overexpressing the ilvBN , ilvCED , ygaZH , and lrp genes was able to produce 7.55 g/liter l -valine from 20 g/liter glucose in batch culture, resulting in a high yield of 0.378 g of l -valine per gram of glucose. These results suggest that an industrially competitive strain can be efficiently developed by metabolic engineering based on combined rational modification, transcriptome profiling, and systems-level in silico analysis.